A Framework for Early-Stage Design Assessment: Integrating Adaptability and Resilience Metrics to Mitigate Building Obsolescence - Beri, Jitvin; Gupta, Priyanka (Journal of Progress in Civil Engineering, 2025)
Building infrastructure and construction is essential to India's rapidly growing economy; in the near future, it is anticipated that approximately 700–900 million square meters of commercial and residential space will need to be built. The Ministry of Housing and Urban Affairs states that estimates indicate the construction industry contributes significantly to India's carbon footprint, creating between 150 and 500 million tonnes of construction and demolition (C&D) polluting waste annually and cannot be managed. Lack of adaptability in the building design program is a major cause of demolition and premature end - of - life stages. In this scenario, there is heightened concern regarding the drastic environmental degradation that could result from failing to prioritise the implementation of sustainable practices from the outset of design and decision - making. In the Life Cycle Assessment (LCA) process, flexibility and adaptability are given immense significance in any project design. This paper highlights the current research gap of unavailability of environmental indicators ‘measure’ aspects such as adaptability and/or flexibility, durability, robustness or resilience. However, these aspects affect the duration of the working life of the building and are therefore, extremely relevant for the minimization of waste and optimisation of the use of resources. Hence, the framework for the assessment of the environmental indicators should take this into consideration from early design stage. Flexibility and adaptability enable buildings to recycle, re - use and upcycle these buildings into urban regeneration projects, and these factors need to be included in the early design stage, and ethos of architectural practice, effectively proving sustainable.